Social Media Marketing Strategies and Their Impact on Brand Equity and Buying Interest in Cake & Bakery - Mariam, Siti; Defran, Hanif Muhammad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Increasing competition in the food industry, especially in the cake and bread sector, encourages companies to increase their marketing competitiveness through social media, requiring marketers who can build strong brands. Even though the number of followers of a company on social media has become a general indicator, it cannot provide a definite picture of how much buying interest these followers have in the products being sold. This research explores the influence of social media marketing activities on brand equity and purchasing Interest in the food industry, especially in cake and bread products. This study takes a quantitative approach by analyzing data collected from the followers of Kumo Cake's Instagram account. By using a straightforward random sample technique, 122 participants from the Jabodetabek region were chosen for the survey. A Structural Equation Model (SEM) is used for the analytical purpose. The study's findings demonstrate that SMM campaigns boost brand equity, which in turn increases purchase interest, and that brand equity influences buy interest in a positive and statistically significant way. These results have important implications for food sector firms looking to improve their social media marketing strategy in order to raise consumer interest in their brands and products.